Shape memory response and hierarchical motion capabilities of 4D printed auxetic structures. (January 2020) - Pandini, Stefano; Inverardi, Nicoletta; Scalet, Giulia; Battini, Davide; Bignotti, Fabio; Marconi, Stefania; Auricchio, Ferdinando
Highlights: 4D printed programmable shape memory polymer-based auxetics are investigated. The shape memory polymer displays the temperature memory effect. A negative 'Poisson's ratio equal to about −0.18 is found. Sequential in-plane and out-of-plane motions of auxetics can be easily programmed. Results are general and can be applied to any auxetic geometry. Abstract: 4D printing refers to a novel trend in the field of active materials, regarding the employment of additive manufacturing to obtain structures presenting inherent complex shapes and shape evolutions under the application of proper stimuli. Such a technique is a powerful tool to realize auxetic structures with customized architectures and programmable/controllable shape change. The present paper proposes 4D printed shape memory polymer-based systems with auxetic structure, capable of hierarchical motion. The systems were prepared starting from a commercial photopolymer by means of stereolithography. The mechanical behavior of the systems was characterized in uniaxial tensile tests, measuring the strains parallel/perpendicular to the load direction. Thanks to a broad glass transition region, the photopolymer displays the so-called "Temperature-Memory Effect" (TME), i.e. the possibility to tailor the thermal trigger of the Shape-Memory Effect (SME) through the deformation temperature. Thermo-mechanical histories were applied to a single unit cell to investigate both the overall shape memory response and the possibility to undergo multiple combined out-of-plane and in-plane motions on the basis of the TME. Obtained results allow discussing the effect of deformation temperatures on the thermal region triggering the SME and show the possibility to exploit the TME to achieve sequential self-deployment of auxetic structures.